Single-step synthesis and interface tuning of core–shell metal–organic framework nanoparticles. Issue 12 (17th February 2021) - Orr, Kieran W. P.; Collins, Sean M.; Reynolds, Emily M.; Nightingale, Frank; Boström, Hanna L. B.; Cassidy, Simon J.; Dawson, Daniel M.; Ashbrook, Sharon E.; Magdysyuk, Oxana V.; Midgley, Paul A.; Goodwin, Andrew L.; Yeung, Hamish H.-M.
Abstract : Core–shell metal–organic framework nanoparticles have been synthesised in which the internal interface and distribution of components is found to be highly tunable using simple variations in reaction conditions. Abstract : Control over the spatial distribution of components in metal–organic frameworks has potential to unlock improved performance and new behaviour in separations, sensing and catalysis. We report an unprecedented single-step synthesis of multi-component metal–organic framework (MOF) nanoparticles based on the canonical ZIF-8 (Zn) system and its Cd analogue, which form with a core–shell structure whose internal interface can be systematically tuned. We use scanning transmission electron microscopy, X-ray energy dispersive spectroscopy and a new composition gradient model to fit high-resolution X-ray diffraction data to show how core–shell composition and interface characteristics are intricately controlled by synthesis temperature and reaction composition. Particle formation is investigated by in situ X-ray diffraction, which reveals that the spatial distribution of components evolves with time and is determined by the interplay of phase stability, crystallisation kinetics and diffusion. This work opens up new possibilities for the control and characterisation of functionality, component distribution and interfaces in MOF-based materials.